Widening and Wilding The Socio-Ecological Dimensions of Peace Experiences from the International Institute on Peace Education: Experiences from the International Institute on Peace Education - Gerson, Janet C.; Knox-Steiner, Stephanie; Pastoors, Dani*el*a (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
In this exploratory conceptual and reflective article, we aim to describe the dynamic yet amorphous socio-ecological dimensions of peace as we have experienced them through the learning ecosystem of the International Institute on Peace Education (IIPE). We begin by naming the threads that brought us to this collaboration, then we build a conceptual mosaic in this pursuit, engaging with peace, modernity, interbeing, and sentipensar. We then describe the learning ecosystem of the IIPE and delve into the mosaic thinking that weaves this ecosystem together. We then engage in a detailed description of an example of IIPE pedagogical experimentation with regenerative peace pedagogies using the workshop on hospicing modernity, our roles, and our reflections on the experience. Finally, we consider how IIPE might enhance, deepen, or further emphasize the socio-ecological dimensions of peace through our relationships with each other, the inner workings of the institute, and the institute’s location in more intentional ways. We consider how this relational socio-ecological dimension of peace might be called regenerative peace education and discuss how these insights might open up peace pedagogy and practices for cultivating dynamic webs of caring relations and generosity of spirit among humans, other living systems and the natural world upon which our survival depends and of which we are a part. We hope that in deeply exploring these considerations using the example of the IIPE, the insights might be relevant to other peace education contexts and endeavors.